Cholinergic basal forebrain neurons regulate vascular dynamics and cerebrospinal fluid flux - Kai-Hsiang Chuang; Xiaoqing Alice Zhou; Ying Xia; Zengmin Li; Lei Qian; Eamonn Eeles; Grace Ngiam; Jurgen Fripp; Elizabeth J. Coulson (Nature Communications)
Abstract Brain waste is cleared via a cerebrospinal fluid (CSF) pathway, the glymphatic system, whose dysfunction may underlie many brain conditions. Previous studies show coherent vascular oscillation, measured by blood oxygenation level-dependent (BOLD) fMRI, couples with CSF inflow to drive fluid flux. Yet, how this coupling is regulated, whether it mediates waste clearance, and why it is impaired remain unclear. Here we demonstrate that cholinergic neurons modulate BOLD-CSF coupling and glymphatic function. We find BOLD-CSF coupling correlates cortical cholinergic activity in aged humans. Lesioning basal forebrain cholinergic neurons in female mice impairs glymphatic efflux and associated changes in BOLD-CSF coupling, arterial pulsation and glymphatic influx. An acetylcholinesterase inhibitor alters these dynamics, primarily through peripheral mechanisms. Our results suggest cholinergic loss impairs glymphatic function by a neurovascular mechanism, potentially contributing to pathological waste accumulation. This may provide a basis for developing diagnostics and treatments for glymphatic dysfunction.